Analysis to supply and demand water for rice cultivation in the ambit of Copallin private conservation area in Amazonas - Cotrina T., Tania E. (2016)
This research develops because to the concern of the population who express that in recent years there has been registered a progressive decrease of water availability in the ambit of Copallín Private Conservation Area, affecting the agricultural activities in the middle and lower basin, mainly rice cultivation. So it is essenti alto evaluate the behavior of supply and demand of water for rice cultivation activity for the period between 1989 and 2007. To estimate the watersupply, we used the abstractions method of the Soil ConservationService (SCS) also known as curve number CN, which has led to obtain annual average flows. To estimate the area of rice crops and then determine the required water demand based on the surface, we used the visual analysis of satellite images using Geographic Information Systems (GIS). There sults show a progressive decrease to the total anual water supply, from 442.79 MMCto435.80 MMC between 1989 and 2007. However, it is enough to cover the total anual wáter demand for rice cultivation amounting to101.21 MMC.